Answer:
![-3 +2y \leq 4x](https://tex.z-dn.net/?f=%20-3%20%2B2y%20%5Cleq%204x)
![2y \leq 4x+3](https://tex.z-dn.net/?f=%202y%20%5Cleq%204x%2B3)
![y \leq 2x + \frac{3}{2}](https://tex.z-dn.net/?f=%20y%20%5Cleq%202x%20%2B%20%5Cfrac%7B3%7D%7B2%7D)
And that's different from the claim of the student that:
![y \geq 2x +\frac{3}{2}](https://tex.z-dn.net/?f=%20y%20%5Cgeq%202x%20%2B%5Cfrac%7B3%7D%7B2%7D)
The error of the student is that he/she changes the sign of the inequality from
to
and that's not possible since we don't multiply both sides of the equation by -1
Step-by-step explanation:
For this case we have the following inequality:
![-3 +2y \leq 4x](https://tex.z-dn.net/?f=%20-3%20%2B2y%20%5Cleq%204x)
We want to rewrite the last expression with y in the left and x in the right so we can begin adding 3 in both sides of the inequality and we got:
![2y \leq 4x+3](https://tex.z-dn.net/?f=%202y%20%5Cleq%204x%2B3)
Now we can divide both sides of the inequality by 2 and we got:
![y \leq 2x + \frac{3}{2}](https://tex.z-dn.net/?f=%20y%20%5Cleq%202x%20%2B%20%5Cfrac%7B3%7D%7B2%7D)
And that's different from the claim of the student that:
![y \geq 2x +\frac{3}{2}](https://tex.z-dn.net/?f=%20y%20%5Cgeq%202x%20%2B%5Cfrac%7B3%7D%7B2%7D)
The error of the student is that he/she changes the sign of the inequality from
to
and that's not possible since we don't multiply both sides of the equation by -1